STRATEGIES AND IMPROVEMENT PRIORITIES AGAINST CONSTRAINTS IMPLEMENTATION OF ROUNDTABLE ON SUSTAINABLE PALM OIL (RSPO) AT PT XYZ PKS C - Caroline; Sukaria Sinulingga; Meilita Tryana Sembiring (CV. RADJA PUBLIKA, 2024)
The Roundtable on Sustainable Palm Oil (RSPO) is a global non-profit organization that focuses on developing and implementing global standards for sustainable palm oil that has a responsibility to protect animals, environments, workers and local communities. PT XYZ – PKS C has obtained RSPO certification on June 13th, 2023. The research objectives are: 1) finding out the obtacles faced in the implementation of RSPO; and 2) looking for effective strategies to overcome the negative impacts of these obstacles. Research was conducted using qualitative and quantitative methods through interviews and AHP (Analytical Hierarchy Process) questionnaires. Results obtained: 1) PT XYZ realizes that the obstacles faced in the adoption of RSPO include: a) Limited Capability and Number of Human Resources, b) Limited Budget Funds/Costs, c) Lack of Coordination and Consultation communication, and d) Legal Regulations; 2) Priority for resolving operational obstacles in implementation of RSPO, including: a) Level 1: Planet, b) Level 2: Principle 2 and 6; 3) Strategies that can be implemented by PT XYZ to overcome obstacles, including: a) following ISO 14001:2015 and ISO 9001:2015 certification; b) Consulting with sustainability teams from other palm oil companies; c) Design a buffer area by planting plants consumed by long-tailed monkeys.